Ectopic pregnancy: one-year retrospective study on clinical, investigational and operative correlation in a tertiary care hospital - Pati, Basant Kumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Ectopic pregnancy is a life-threatening emergency which is one of the important cause of maternal mortality. Ectopic pregnancy must be suspected in any woman in the reproductive age group, presenting with lower abdominal pain or vaginal bleeding. Our aim was to review all cases of ectopic pregnancy and determine the incidence, high risk factors, types of clinical presentation and mode of management. Methods: This was a retrospective cohort study, conducted at a tertiary care hospital. Medical records of all women with an ectopic pregnancy between 2016 and 2017 were seen. Demographic data, risk factors, clinical features, and mode of management were noted. Results: 90 patients, diagnosed with ectopic pregnancy during last one year was included in the present study, with an incidence of 1.2%. Majority of women were aged 20-30 years (50%). 74.4% cases were ruptured ectopic. The most common risk factors were previous ectopic (50%) and pelvic inflammatory disease (17.7%). Lower abdominal pain was seen in 80 (40.3%) patients. Majority of patients (91.1%) had tubal ectopic pregnancies. Most common mode of treatment was salpingectomy. Conclusions: Risk factors for ectopic pregnancy must be enquired and early diagnosis and management to be done to avoid maternal morbidity and mortality.